Javanese medaka (Oryzias javanicus Bleeker, 1854) as potential model organism for aeromoniasis and vibriosis study in fish - Azmai, Mohammad Noor Amal; Mohd Roseli, Mohd Fauzul Aidil; Sutra, Jumria; Roslan, Syuhada; Mazlan, Siti Nur Khamisah; Basri, Lukman; Lee, Jing Yie; Mohamad, Nurliyana; Ismail, Ahmad; Saad, Mohd Zamri; Md Yasin, Ina Salwany; Nasruddin, Nurrul Shaqinah (Universiti Putra Malaysia Press, 2019)
Javanese medaka is a small tropical fish that has been widely used as a test organism in ecology, toxicology and ecotoxicology, but less in fish-pathogen related study. This study evaluates the capability of Javanese medaka as an alternative model organism for aeromoniasis and vibriosis study in fish. Javanese medakas were infected with different concentrations of Aeromonas hydrophila, Vibrio alginolyticus and V. harveyi via intraperitoneal (IP) and immersion (IMM) routes. Following the infections, the LD50- 240h of all bacteria to Javanese medaka were observed lower in IP, compared with IMM route. In IP route, the LD50-240h ranged from 2.1 × 104 CFU/mL for V. harveyi to 2.5 × 107 CFU/mL for A. hydrophila. However, for IMM route, the range was from 6.6 × 107 CFU/mL for V. harveyi to 1.1 × 109 CFU/ mL for V. alginolyticus. The clinical signs, gross lesions and histopathological changes of Javanese medakas infected by either IP or IMM routes of all the pathogens were similarly observed in the real host of the pathogen. Moreover, in IP route, most of the fish mortalities (88.9%) were observed within ≤ 120 hours post infection (hpi), while for IMM, most of the mortalities (50.6%) were witnessed beyond 120 hpi, indicating the acute infection for IP compared to IMM route. This study highlights the potential utilization of Javanese medaka as another valuable in vivo model organism for bacterial diseases study in fish.